THE GENUS JARANDERSONIA KOSTERM. - A. J. G. H. KOSTERMANS (REINWARDTIA, 1970)
Since its inception-in 1960, the monotypic genus Jarandersonia has been enlarged with a new species in 1962 (J. spinulosa).Since then two more collections have come to my attention, which represent undescribed species, one (S. 15561) distributed as Bombacaceae,the other (San 27885) as Rinorea cf. elmeri Merr.Moreover Dr. Anderson of the Forest Department, Kuching, Sarawak,in whose honour the genus was named, wrote me that Brownlowia clemensiae had been collected with fruit,which proved in to be a Jarandersonia, a fact, already suggested by Dr.P.Ashton in a draft MSS prepared for the Manual of Non-Dipterocarp Trees of Sarawak.Together with Dr. Anderson I had the opportunity to see a mature tree of the latter species near Kuching in June 1969 (S. 25415).The genus comprises now 5 species (J. clemensiae, parvifolia, purseglovei, rinoreoides and spinulosa).